2021
DOI: 10.3758/s13423-021-01922-z
|View full text |Cite
|
Sign up to set email alerts
|

Memorisation and implicit perceptual learning are enhanced for preferred musical intervals and chords

Abstract: Is it true that we learn better what we like? Current neuroaesthetic and neurocomputational models of aesthetic appreciation postulate the existence of a correlation between aesthetic appreciation and learning. However, even though aesthetic appreciation has been associated with attentional enhancements, systematic evidence demonstrating its influence on learning processes is still lacking. Here, in two experiments, we investigated the relationship between aesthetic preferences for consonance versus dissonance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 103 publications
(174 reference statements)
1
14
0
Order By: Relevance
“…As it has previously suggested (for a detailed discussion see Sarasso et al, 2021) contextual and cultural factors, as well as subjective experience (e.g., musical expertise) might modulate the estimated precision of consonant and dissonant sounds. It might be that different participants interpreted different sounds (fifths vs. tritones) as more and less precise.…”
Section: Discussionmentioning
confidence: 89%
See 2 more Smart Citations
“…As it has previously suggested (for a detailed discussion see Sarasso et al, 2021) contextual and cultural factors, as well as subjective experience (e.g., musical expertise) might modulate the estimated precision of consonant and dissonant sounds. It might be that different participants interpreted different sounds (fifths vs. tritones) as more and less precise.…”
Section: Discussionmentioning
confidence: 89%
“…We propose that aesthetic appreciation might be considered as a feedback signal facilitating the discrimination of informationally profitable stimuli (inducing larger prediction updates) from “unlearnable” noisy signals (Sarasso, Neppi-Modona, et al, 2020; Sarasso et al, 2021). According to this interpretation, aesthetic pleasure might motivate us to select and engage in “informationally profitable” perceptual activities, independently from material or social reward (Chatterjee & Vartanian, 2016; Pearce et al, 2016).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Each block started with the Memorization Phase (duration: 2 min), where subjects were asked to pay attention to the spatial configuration of the objects with the aim of learning and remembering it. Following the Memorization Phase, subjects were asked to perform a distraction task (a pitch discrimination task similar to Sarasso et al, 2019 ; Sarasso et al, 2021 , see also Sarasso et al, 2020 ) for 5 min, to avoid a rehearsal effect on subsequent memory performance. In the final Recall Phase, subjects were asked to place 10 (out of 16) objects in the exact position displayed in the Memorization Phase.…”
Section: Methodsmentioning
confidence: 99%
“…In a series of experiments ( Sarasso et al, 2021a , b ) we found that widely acknowledged electrophysiological indexes of implicit perceptual learning of sensory regularities, such as the mismatch negativity (MMN), were enhanced for subjectively more appreciated musical chords. The MMN negativity is a differential wave obtained by subtracting EEG responses to standard events to those elicited by deviant events.…”
Section: Aesthetics and Knowledge/changementioning
confidence: 99%